Ameliorative Effect of Vitamin D on Articular Cartilage Thickness in Arthritic Rat Model - Ayesha Shahid; Huma Beenish; Tooba Khurshid; Amber Rashid; Uzma Shahid; Maimoona Khan (Life and Science)
Objective: To determine the protective effect of vitamin D on the articular cartilage of formalin-induced arthritis in rats. Study Design: Lab–based Experimental study. Place and Duration of Study: The study was carried out at the Department of Anatomy, Islamic International Medical College from September 2020 to September 2021. Methods: We randomly split thirty adult male albino rats weighing between 250 and 300 grams into three groups. (10 in total). On days 1 and 3 of the experiment, formaldehyde was subcutaneously injected into the right paw of every animal, with the exception of those in group A. The usual rat food was given to the rats in Groups A and B. Throughout the trial, Rats in group C were given vitamin D 4000IU/kg orally by adding cholecalciferol (Vitamin D3) injection in a standard diet for 28 days. All of the animals were dissected after the experiment, and the right hind leg was taken out, processed, and stained with H&E for a microscopic assessment of the thickness of the unclarified cartilage. Version 21 of SPSS was used to analyze the results. Results: The oral administration of vitamin D exhibited a significant increase in unclarified cartilage thickness on intergroup comparison. Conclusion: Vitamin D is an effective antiarthritic agent in ameliorating the thickness of articular cartilage thickness in arthritic rat models.